Value chain development to benefit smallholders in Ghana: The effectiveness of selected interventions - Kolavalli, Shashidhara; Agandin, John; Ampofo, Aaron; Kemeze, Francis; Amewu, Sena (International Food Policy Research Institute, 2020)
This study examines interventions in two agricultural development projects in Ghana which aimed to build competitiveness of selected value chains to generate growth and reduce poverty – the Northern Rural Growth Project, implemented between 2009 and 2016, and the Market Oriented Agriculture Programme, which began in 2004 and is still in place. These projects aimed to sustainably increase rural households’ income through the development of inclusive and profitable agricultural commodity and food value chains to generate agricultural surpluses and to benefit from improved access to remunerative markets. In this study, the efficacy of four sorts of value chain interventions implemented by the two projects are examined in the context of the strengthening maize, pineapple, mango, and citrus value chains: • Facilitating interactions among value chain actors to encourage technical and institutional innovations, • Improving the operations of individual actors, such as producers, service providers, traders, and processors; • Helping develop new services for producers or initiating new producer institutions; and • Improving infrastructure. The study sought to identify how, where, and when might it be appropriate to intervene in value chains, particularly to benefit smallholders. While the lessons from this study do not comprehensively answer these questions, a better understanding is provided on the reasons behind the outcomes the projects attained in seeking to strengthen agricultural commodity value chains and some guidance is offered on how interventions aimed at doing so should be designed.